MATHEMATICAL CONCEPTS FOR ELEMENTARY TO SECONDARY SCHOOL FOUND IN THE AL-JABBAR MOSQUE: AN ETHNOMATHEMATICS STUDY - Nur Riski Hasanah; Turmudi Turmudi; Dadang Juandi (Universitas Lambung Mangkurat, 2024)
A meaningful learning process for students can be done by linking mathematics with real contexts and applied with approaches that are in accordance with the characteristics of students. Ethnomathematics studies include various forms of cultural products related to mathematical concepts and activities in the form of buildings, artefacts, social activities, or in various cultural products. In this study, mathematical concepts will be studied in the form of buildings architecture, namely the Al-Jabbar mosque. This research aims to find mathematical concepts in the Al-Jabbar mosque that can be raised in the learning process in the classroom. The method used is qualitative research. Data analysis techniques with literature study, documentation, field observation, and document analysis. The results of the study are many mathematical concepts contained in the Al-Jabbar mosque and can be raised in classroom learning, namely the concept of area under a parabolic curve, parabolic curve equation, integral, geometry transformation (rotation, dilation, reflection, translation), one-dimensional geometry concepts (point, lines and angles), two-dimensional geometry (various triangles, quadrilaterals, circles), three-dimensional geometry (Hemisphere, prisms, tubes), and number patterns. All concepts found are important materials in learning mathematics in elementary to secondary schools so that they can be integrated in the mathematics learning. Keywords: Ethnomathematics, Al-Jabbar Mosque, Mathematical Concepts, Elementary School, Secondary School.